Pengembangan Sistem Monitoring Berbasis Internet of Things untuk Perawatan Berkala Kendaraan dan Alat Berat dengan Fitur Pelaporan Terintegrasi dan GPS - Pratama, Handika Yoga; Surojo; M. Hilmi; Bahiuddin, Irfan (Jurnal Teknologi dan Rekayasa Alat Berat, 2025)
This study aims to develop an Internet of Things (IoT)-based hourmeter monitoring system to improve the efficiency and accuracy of periodic maintenance for vehicles and heavy equipment. The system is designed to integrate with a website that enables real-time monitoring of operating hours, reporting, and maintenance notifications. Testing was conducted on one light vehicle and one heavy equipment unit over a period of four days. The developed system was able to accurately record operating time, provide maintenance notifications via alarms, and monitor the unit’s location and performance using GPS data. The test results showed that the system successfully recorded travel distance and average speed, with the light vehicle achieving 14.2 km and 11.9 km/h, while the heavy equipment recorded 1.98 km and 7.17 km/h. The integration of hourmeter monitoring and GPS features proved to enhance supervision effectiveness and maintenance schedule prediction, thus potentially reducing the risk of damage and downtime. This system offers an innovative solution that can be adopted in the heavy equipment industry to support more optimal maintenance management.